The - Fjeldstad, Mary C. (Thomson/Wadsworth, 2006)
Good reading, thinking, and writing abilities are essential to college success. With engaging articles, essays, stories, textbook chapters, and writing exercises, THE THOUGHTFUL READER helps you develop these crucial skills. Carefully selected readings introduce you to the types of materials you will encounter in your college courses and your adult life. Review, discussion, and exam questions are presented so that you can see what you will face in an actual course. Tools such as Thinking about the Theme, Introduction to the Reading Selection, Vocabulary, Guide Questions, Applications, Writing Assignments, and Making Connections are designed to help you improve your reading and writing skills and succeed in your college courses